Film behaviour of natural rubber latex treated with banana skin - Goh, Tok Mun (2012)
Natural rubber latex (NRL) is the milky fluid obtained from the Hevea Brasiliensis tree. Proteins the naturally occurring components of NRL have been related to hypersensitivity. Therefore, study on protein in NRL films is crucial. It created one of the biggest markets for improved in the glove industry. Bio-based polymer such as soy bean and milk has been investigated as a component in plastic. However, it is costly. As starch-based materials proved to be good biodegradable sources, banana skins are chosen. Large quantities of waste generated from banana peels will cause serious problems if disposed indiscriminately. It can be new sources pushes to brand new trial in polymer industry for banana skin on the study of film behavior. In the present study, banana skin powder is introduced in NRL due to its good sources of nutrients where Maillard reaction believed in cross link with the protein in NRL thus reduces protein contributed by banana skin. Other than that, banana skin is introduced to increasing the mechanical properties. Five samples conducted in this research by varying the banana skin loading, which are 0%, 5%, 10%, 15% and 20%. Lowry method is been used to measures total protein content. Result showed that protein content in NRL film increase with the banana skin loading. The highest protein content found to be latex film treated with 15% of banana skin loading. Based on the ASTM recommends their standards for medical gloves that all examination and surgical gloves should contains less than 200 .tg/dm 2 , latex film treated with banana skin need undergoes proper leaching during the process of production to reduce the extractable protein (EP) content. For mechanical properties, dumbbell shaped samples are cut from the mould sheets according to ASTM D412. Tensile strength increased up to 10% filler loading. Further increase in filler loading after 10% resulted in a reduction of tensile properties. While for tensile modulus, MlOO, M300 and M500 increased with the filler loading. The results obtained in this research intended help boosts development in the production of glove industry in future. As in conclusion, study on film behavior of NRL treated with banana skin leads to green environment.